Effect of degree of saturation on stresses and pore water pressure in the subgrade layer caused by railway track loading - Mohammed Y. Fattah; Qutaiba G. Majeed; Hassan H. Joni (Railway Sciences)
Purpose – The experiments of this study investigated the effect of the subgrade degree of saturation on the value of the stresses generated on the surface and the middle (vertical and lateral stresses). The objectives of this study can be identified by studying the effect of subgrade layer degree of saturation variation, load amplitude and load frequency on the transmitted stresses through the ballast layer to the subgrade layer and the stress distribution inside it and investigating the excess pore water pressure development in the clay layer in the case of a fully saturated subgrade layer and the change in matric suction in the case of an unsaturated subgrade layer. Design/methodology/approach – Thirty-six laboratory experiments were conducted using approximately half-scale replicas of real railways, with an iron box measuring 1.5 x 1.0 × 1.0 m. Inside the box, a 0.5 m thick layer of clay soil representing the base layer was built. Above it is a 0.2 m thick ballast layer made of crushed stone, and on top of that is a 0.8 m long rail line supported by three 0.9 m (0.1 × 0.1 m) slipper beams. The subgrade layer has been built at the following various saturation levels: 100, 80, 70 and 60%. Experiments were conducted with various frequencies of 1, 2 and 4 Hz with load amplitudes of 15, 25 and 35 kN. Findings – The results of the study demonstrated that as the subgrade degree of saturation decreased from 100 to 60%, the ratio of stress in the lateral direction to stress in the vertical direction generated in the middle of the subgrade layer decreased as well. On average, this ratio changed from approximately 0.75 to approximately 0.65. Originality/value – The study discovered that as the test proceeded and the number of cycles increased, the value of negative water pressure (matric suction) in the case of unsaturated subgrade soils declined. The frequency of loads had no bearing on the ratio of decline in matric suction values, which was greater under a larger load amplitude than a lower one. As the test progressed (as the number of cycles increased), the matric suction dropped. For larger load amplitudes, there is a greater shift in matric suction. The change in matric suction is greater at higher saturation levels than it is at lower saturation levels. Furthermore, it is seen that the load frequency value has no bearing on how the matric suction changes. For all load frequencies and subgrade layer saturation levels, the track panel settlement rises with the load amplitude. Higher load frequency and saturation levels have a greater impact.